Automated measurement of vocal fold vibratory asymmetry from high-speed videoendoscopy recordings - Mehta, Daryush D. (2010)
PURPOSE: In prior work, a manually derived measure of vocal fold vibratory phase asymmetry correlated to varying degrees with visual judgments made from laryngeal high-speed videoendoscopy (HSV) recordings. The current investigation extended upon this work by establishing an automated HSV-based framework to quantify three categories of vocal fold vibratory asymmetry. METHOD: HSV-based analysis provided for cycle-to-cycle estimates of left-right phase asymmetry, left-right amplitude asymmetry, and axis shift during glottal closure for 52 normal speakers producing comfortable and pressed phonation. An initial cross validation of the automated left-right phase asymmetry measure was performed by correlating the measure with other objective and subjective assessments of phase asymmetry. RESULTS: Vocal fold vibratory asymmetry was exhibited to a similar extent in both comfortable and pressed phonations. The automated measure of left-right phase asymmetry strongly correlated with manually derived measures and moderately correlated with visual-perceptual ratings. Correlations with the visual-perceptual ratings remained relatively consistent as the automated measure was derived from kymograms taken at different glottal locations. CONCLUSIONS: An automated HSV-based framework for the quantification of vocal fold vibratory asymmetry was developed and initially validated. This framework serves as a platform for investigating relationships between vocal fold tissue motion and acoustic measures of voice function.